Historia, política y responsabilidad: Óscar Terán y la autocrítica entre los intelectuales de izquierda en Argentina - Starcenbaum, Marcelo (2014)
This work aims to reconstruct the genealogy of self-criticism within the intellectual circles of Argentinian left from the itinerary of Oscar Terán, one of its mains characters and historians. We review his main historiographical work and interventions in political and cultural magazines to delineate breaks and continuities in the constructions of a story that gives accounts of the process of political radicalization in Argentina. We will see how the story moves from a contemplative reading in the 80s to a closing operation in the 90s and early 21st century.